Implementation of control and SCADA system: Case study of Allen Bradley PLC by using WirelessHART to temperature control and device diagnostic - Teerawat Thepmanee; Sawai Pongswatd; Farzin Asadi; Prapart Ukakimaparn (My University, 2021)
System integration for process automation promoted the technologies that were accessed to functions and data of field device, controller, and SCADA system. In addition, the data from filed devices can apply to solve device diagnostic and preventive maintenance. This paper describes the practical technique to configure and implement of control and SCADA system that focus on integration of field device, PLC controller, and SCADA system. The paper presents case study of Allen-Bradley (AB) PLC by using WirelessHART device to temperature control and device diagnostic through SCADA system. PLC's input/output (I/O) modules are installed that consists of Modbus module, digital I/O module, analog I/O module. In addition, Prosoft configuration builder and Studio 5000 software are new software to build add on Modbus instruction and ladder diagrams, respectively. The experiments perform in case study of temperature control by using Proportional–Integral–Derivative (PID) function in the AB PLC. Wonderware InTouch SCADA software is implemented to monitor the process mimic, trend, and alarm. Moreover, the technique can support the operators and engineers to make decision for process control and devices diagnostic.
Keywords: Modbus; SCADA; Experimental Learning in Engineering